Hydrotropism in lateral but not in pivotal roots of desert plant species under simulated natural conditions - Guevara, Aranzazú (2014)
Aims Root hydrotropism has been widely studied in seedling radicles through artificial experiments that reduce the influence of gravity and soil. In this work we aimed to study hydrotropism of primary lateral and pivotal roots in developed root systems of desert plants under simulated natural conditions. Methods We grew Bulnesia retama Griseb. (non phreatophyte), Prosopis flexuosa DC. (facultative phreatophyte) and Prosopis alpataco Phil.(obligate phreatophyte) seedlings in observation boxes with sand. Lateral and pivotal roots were stimulated by lateral water gradients and hydrotropic responses, root proliferation and root : shoot ratios were measured. Results We found that 65 ± 15 % of lateral roots that grew in response to water gradients in B. retama, 84 ± 8 % in P. flexuosa and 88 ± 8 % in P. alpataco displayed hydrotropism. Conversely, pivotal roots did not show hydrotropic growth. This was accompanied by root proliferation inside water patches, and biomass partitioning to shoot growth. Conclusions Our results provide evidence that root hydrotropism is a relevant response that could occur in nature. Lateral and pivotal roots manifest different hydrotropic responses under the conditions assayed. The combination of hydrotropism and precise root proliferation can shape root architecture, leading to optimum water patch exploration.